Coordination Chemistry of Ir with Chelating Ligands Containing a Xanthine‐Derived, Protic N‐Heterocyclic Carbene (NHC) Moiety. Issue 34 (27th October 2022) - Bevilacqua, Matteo; Giuso, Valerio; Rancan, Marzio; Armelao, Lidia; Graiff, Claudia; Baratta, Walter; Di Marco, Valerio; Biffis, Andrea
Abstract: A series of protic N‐heterocyclic carbene ligand precursors based on theophylline or adenine has been prepared, and the reactivity and coordination chemistry of these proligands towards iridium(III) centers has been investigated. Complex formation appears to be highly dependent on the proligand structure. In one case, a particularly stable complex is formed that enables fully reversible protonation/deprotonation of the coordinated NHC moiety. The acidity constant of the protonated complex was consequently determined. Abstract : A chelating proligand with a direct bond between a theophylline moiety and a pyridyl group affords a very stable iridium(III) complex that can reversibly undergo protonation at the free xanthine nitrogen atom. The acidity constant of the resulting protic NHC complex has been determined.